A green process for extraction of omega 3 fish oil from tuna byproducts - Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Nik Abdul Rahman, Norulaini; A. K. M., Omar (2013)
Fish industry discarded a great amount of fish byproducts as processing left over every year. Proper utilization of these byproducts could increases the overall value of the catch and decreases environmental pollution. Tuna fishes are mainly traded as canned or frozen food product. During canning process of tuna fish, a large amount (~60% of total weight) of solid wastes were generated as by-products which contain omega 3 fish oil that is beneficial for human health. Conventional solvent extractions are generally employed to obtain fish oil; while often introduces contaminants that must be removed later. Supercritical carbon dioxide (SC-CO2) extraction is regarded as green process which offers a new opportunity for the solution of separation problem as it is nontoxic, environmental-friendly, residue-free and one step method. The objective of this study was to identify an extraction technique using SCCO2 to recover the maximum oil yield from tuna fish byproducts using the minimum amount of CO2. The extraction were performed at temperature 45 to 65 0C, pressure 20 to 40 MPa and flow rate 2 to 4 ml min-1, where 65 0C/40 MPa/4 ml min-1 gave the highest yield of 20.6, 35.5, and 30.8 g/ 100 g sample (dry basis) for the continuous, cosolvent, and soaking techniques of SCCO2, respectively. The yields were closer to the yield of conventional Soxhlet (36.2%) method. The results indicated that, oil yield increased with pressure and temperature. The poor extractability by continuous extraction technique may be due to mass transfer limitations within the solid matrix. The enhanced extractability by cosolvent extraction can be attributed to enhanced solvent power. Docosahexaenoic acid (DHA) was characteristically the major omega 3 fish oil accounting for 17.01-19.90% in head, 15.73-17.290% in skin and 14.31- 16.06% in viscera of total fatty acids. The highest CO2 consumption was found in continuous technique (943.5 g), followed by soaking (471.7 g), and co-solvent technique (258.6 g) respectively. On the whole, it was observed that co-solvent method of SC-CO2 is an effective method to extract fish oil that is rich in omega-3 fish oil from tuna byproducts.